2018
DOI: 10.1002/ece3.4709
|View full text |Cite
|
Sign up to set email alerts
|

The Gambian epauletted fruit bat shows increased genetic divergence in the Ethiopian highlands and in an area of rapid urbanization

Abstract: The Gambian epauletted fruit bat (Epomophorus gambianus) is an abundant species that roosts in both urban and rural settings. The possible role of E. gambianus as a reservoir host of zoonotic diseases underlines the need to better understand the species movement patterns. So far, neither observational nor phylogenetic studies have identified the dispersal range or behavior of this species. Comparative analyses of mitochondrial and nuclear markers from 20 localities across the known distribution of E. gambianus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Moreover, the Schloss formula performs notably poorly for bats: for example, it would assign the largest bat in our study, the Indian flying fox ( Pteropus giganteus ), a dispersal capacity lower than that of the gray dwarf hamster ( Cricetulus migratorius ). Bats were instead given full dispersal in all scenarios: given significant evidence that some bat species regularly cover continental distances 43,44 , and that isolation by distance is uncommon within many bats’ ranges 46 , we felt this was a defensible assumption for modeling purposes. Moving forward, the rapid range shifts already observed in many bat species (see main text) could provide an empirical reference point to fit a new allometric scaling curve (after standardizing those results for the studies’ many different methodologies).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the Schloss formula performs notably poorly for bats: for example, it would assign the largest bat in our study, the Indian flying fox ( Pteropus giganteus ), a dispersal capacity lower than that of the gray dwarf hamster ( Cricetulus migratorius ). Bats were instead given full dispersal in all scenarios: given significant evidence that some bat species regularly cover continental distances 43,44 , and that isolation by distance is uncommon within many bats’ ranges 46 , we felt this was a defensible assumption for modeling purposes. Moving forward, the rapid range shifts already observed in many bat species (see main text) could provide an empirical reference point to fit a new allometric scaling curve (after standardizing those results for the studies’ many different methodologies).…”
Section: Methodsmentioning
confidence: 99%
“…Because trophic position and body size determine dispersal capacity, carnivores account for a disproportionate number of first encounters, while ungulates and rodents have slightly fewer first encounters than expected at random (ED Figure 6) Spatial patterns also changed dramatically when dispersal constraints were added, with the majority of first encounters and cross-species viral transmission events occurring in southeast Asia (Figure 1B, ED Figures 4, 5). This viral sharing hotspot is driven disproportionately by bats, because their dispersal was left unconstrained; we made this choice given their exclusion from the original study 31 , genetic evidence that flight allows bats—and their viruses—to circulate at continental levels 43,44 , and data suggesting that bat distributions are already undergoing disproportionately rapid shifts 45 . Bats account for 87% of first encounters after constraining dispersal, and dominate the spatial pattern, with most of their first encounters restricted to southeast Asia (Figure 2).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phylogenetic studies revealed that the Ethiopian populations are divergent from all other populations of E. gambianus , possibly due to the Ethiopian highlands (over 3,000 m a.s.l.) and numerous water bodies preventing gene flow between the two populations (see Riesle‐Sbarbaro et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Among mammals, bats (order Chiroptera) represent the only truly volant group and may provide an opportunity to test hypotheses about the role of dispersal in maintaining panmixia. Several species of bats have been reported to show patterns of panmixia including Tadarida brasiliensis in North America (Russell et al, 2005;Speer et al, 2017) as well as Pteropus sp., Nyctalus noctula, Rousettus lesche naultii, Cynopterus sphinx, Eptesicus serotinus, and Epomophorus gambianus in the Old World (Webb and Tidemann, 1996;Petit and Mayer, 1999;Chen et al, 2010;Peel et al, 2013;Moussy et al, 2015;Riesle-Sbarbaro et al, 2018). Despite these examples, panmixia is thought to be relatively rare in bats, with most species exhibiting patterning of genetic structure across their range (Juste et al, 2009;Clare et al, 2013;Stoffberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%